The Influence of Brand Awareness, Brand Image Recognition on Brand Loyalty with the Intervening Mediation of Brand Trust and Brand Love on Samsung Smartphone Products in Indonesia - Eka Ayu Safitri; Albari (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
This research explains the influence of brand awareness, brand image, brand trust, brand love on brand loyalty of Samsung smartphones in Indonesia. Globalization has brought about changes in the world of technology, one of which is the Samsung folding smartphone model. This research used 195 samples. Sampling used a non-probability method with convenience sampling techniques. The analysis techniques used are structural equation modeling (SEM) and AMOS. The research results concluded that there is an influence of: brand awareness on brand image; brand image impacts brand trust; brand trust influences brand love; brand trust impacts brand loyalty; brand love influences brand loyalty. This research also shows that there is no influence of: brand awareness on brand trust; brand awareness has no effect on brand love; brand image has no impact on brand love; brand awareness has no impact on brand loyalty; and brand image has no impact on brand loyalty.